Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If A, then B. If B, then C [#permalink]
07 Sep 2010, 16:56

4

This post received KUDOS

kimakim wrote:

If A, then B. If B, then C. If C, then D. If all of the statements above are true, which of the following must also be true?

(A) If D, then A. (B) If not B, then not C. (C) If not D, then not A. (D) If D, then E. (E) If not A, then not D.

Why is the official answer C ?

For example, choice B could be correct too. If not B then not C.

We're given A -> B, B -> C, and C -> D, and told they're all true. Since they're all true, you can say A -> D. Then by the law of contrapositive, ~D -> ~A. The answer is (C).

(B) isn't correct - this is the inverse of B -> C and does not have the same truth table.

Re: If A, then B. If B, then C [#permalink]
07 Sep 2010, 21:24

TehJay wrote:

kimakim wrote:

We're given A -> B, B -> C, and C -> D, and told they're all true. Since they're all true, you can say A -> D. Then by the law of contrapositive, ~D -> ~A. The answer is (C).

(B) isn't correct - this is the inverse of B -> C and does not have the same truth table.

Yes, the logic is right, if we assume that ALL of the statement should be exist at the same time. But consider if there is only C. Then C->D, and we don;t need A or B to come up with D. Hence if "not D" doesn't imply "not A".

On the other hand answer B "If not B then not C" is right, when we assume that all statements can exist independently of each other.

Re: If A, then B. If B, then C [#permalink]
08 Sep 2010, 01:30

2

This post received KUDOS

kimakim wrote:

TehJay wrote:

kimakim wrote:

We're given A -> B, B -> C, and C -> D, and told they're all true. Since they're all true, you can say A -> D. Then by the law of contrapositive, ~D -> ~A. The answer is (C).

(B) isn't correct - this is the inverse of B -> C and does not have the same truth table.

Yes, the logic is right, if we assume that ALL of the statement should be exist at the same time. But consider if there is only C. Then C->D, and we don;t need A or B to come up with D. Hence if "not D" doesn't imply "not A".

On the other hand answer B "If not B then not C" is right, when we assume that all statements can exist independently of each other.

So, I am still confused

You're told that all of them are true, so you can't just take them independently and pretend that A doesn't exist. Also, irregardless of whether you're looking at A or not, (B) cannot be correct. This is the logical inverse, which is a fallacy. In logic, when dealing with implications, p -> q is equivalent to ~q -> ~p, but not equivalent to ~p -> ~q (inverse) or q -> p (converse). To see this, you can draw up the truth tables:

Re: If A, then B. If B, then C [#permalink]
08 Sep 2010, 06:50

TehJay wrote:

kimakim wrote:

If A, then B. If B, then C. If C, then D. If all of the statements above are true, which of the following must also be true?

(A) If D, then A. (B) If not B, then not C. (C) If not D, then not A. (D) If D, then E. (E) If not A, then not D.

Why is the official answer C ?

For example, choice B could be correct too. If not B then not C.

We're given A -> B, B -> C, and C -> D, and told they're all true. Since they're all true, you can say A -> D. Then by the law of contrapositive, ~D -> ~A. The answer is (C).

(B) isn't correct - this is the inverse of B -> C and does not have the same truth table.

Re: If A, then B. If B, then C [#permalink]
08 Sep 2010, 07:29

2

This post received KUDOS

utin wrote:

TehJay wrote:

kimakim wrote:

If A, then B. If B, then C. If C, then D. If all of the statements above are true, which of the following must also be true?

(A) If D, then A. (B) If not B, then not C. (C) If not D, then not A. (D) If D, then E. (E) If not A, then not D.

Why is the official answer C ?

For example, choice B could be correct too. If not B then not C.

We're given A -> B, B -> C, and C -> D, and told they're all true. Since they're all true, you can say A -> D. Then by the law of contrapositive, ~D -> ~A. The answer is (C).

(B) isn't correct - this is the inverse of B -> C and does not have the same truth table.

CAN'T UNDERSTAND STILL!!!

Ok, consider a simple example:

If I eat dinner now, I will eat dessert later. (A -> B)

You're told this is a TRUE statement - in other words, eating dinner absolutely, positively, no question about it, 100% results in eating dessert after. There's no possible situation that can exist where I will eat dinner now and then NOT eat dessert later.

Now consider the below statements:

If don't eat dessert later, I didn't eat dinner now. (contrapositive: ~B -> ~A)

Since we KNOW FOR A FACT that eating dinner now results in eating dessert later, we can conclude without a doubt that if I don't eat dessert, I most definitely did not eat dinner (because if I had eaten dinner, I would have eaten dessert). This is called the contrapositive and is logically equivalent to the original statement. (This is answer C)

If I don't eat dinner now, I won't eat dessert later. (inverse: ~A -> ~B)

We know for a fact that eating dinner will lead to eating dessert. However, we know absolutely nothing about the result of NOT eating dinner. I didn't say to you that I would ONLY eat dessert if I eat dinner first - only that I would definitely eat it after eating dinner. This statement is not logically equivalent to the original. This is called the inverse, and is answer B.

Re: If A, then B. If B, then C [#permalink]
18 Sep 2010, 11:14

1

This post received KUDOS

I learned this today (forgot the original poster but kudos to him). His/her quote went as If A then B , could be rephrased as if Not B then Not A and if B then may be A.

Take the example of: If I am in France, I am in Europe

If I am not in Europe, I am not in France. ( Not B then Not A)

If I am in Europe, I may be in France ( B then may be A).

All other violate this logical rule or add extra information.

So in the given example by reversing all the signs we get.... ~D => ~C ~C => ~B ~B => ~A Thus simply substituting.... ~D => ~A

Re: If A, then B. If B, then C. If C, then D. If all of the [#permalink]
25 Jun 2012, 09:35

Take A, B, C & D as people. 1. A --> B: If Alice comes then Bella will come. 2. B --> C: If Bella comes then Charlie will come. 3. C --> D: If Charlie comes then Dan will come.

Now, per OA, if Dan doesn't come, what impact does it have on Alice?

Re: If A, then B. If B, then C. If C, then D. If all of the [#permalink]
09 Oct 2013, 17:32

Hello from the GMAT Club VerbalBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.

gmatclubot

Re: If A, then B. If B, then C. If C, then D. If all of the
[#permalink]
09 Oct 2013, 17:32